Real, visible, here: Bisexual+ visibility in Western Australia - Farquhar, Misty; Dau, Duc (2020)
The authors of the article run Bisexual+ Community Perth, a grassroots collective that works to increase bisexual+ visibility and community connection in Western Australia. This article begins by providing an evidence-base for bisexual+ activism, much of it based on the poorer mental health outcomes of bisexual+ people and the pervasive invisibility of bisexual+ people in both LGBTIQ+ communities and activism. Drawing on the work of Bisexual+ Community Perth, the article then offers a practical example of community-building as activism. It explores how collective mobilisation, bridge building, and alliances can be leveraged to make a difference in a local context, and discusses some of the challenges faced in sustaining this work. Throughout the article, the lived experiences of Bisexual+ Community Perth members are included to bring a richness to our account of the work, and to increase empathy towards bisexual+ people in general.